Activation of Human T-Helper/Inducer Cell, T-Cytotoxic Cell, B-Cell, and Natural Killer (NK)-Cells and induction of Natural Killer Cell Activity against K562 Chronic Myeloid Leukemia Cells with Modified Citrus Pectin - Hotchkiss Arland; Wilk Barry J; Ramachandran Cheppail; Chau Hoa; Eliaz Isaac; Melnick Steven J (BMC, 2011)
Abstract Background Modified citrus pectin (MCP) is known for its anti-cancer effects and its ability to be absorbed and circulated in the human body. In this report we tested the ability of MCP to induce the activation of human blood lymphocyte subsets like T, B and NK-cells. Methods MCP treated human blood samples were incubated with specific antibody combinations and analyzed in a flow cytometer using a 3-color protocol. To test functionality of the activated NK-cells, isolated normal lymphocytes were treated with increasing concentrations of MCP. Log-phase PKH26-labeled K562 leukemic cells were added to the lymphocytes and incubated for 4 h. The mixture was stained with FITC-labeled active form of caspase 3 antibody and analyzed by a 2-color flow cytometry protocol. The percentage of K562 cells positive for PKH26 and FITC were calculated as the dead cells induced by NK-cells. Monosaccharide analysis of the MCP was performed by high-performance anion-exchange chromatography with pulse amperometric detection (HPAEC-PAD). Results MCP activated T-cytotoxic cells and B-cell in a dose-dependent manner, and induced significant dose-dependent activation of NK-cells. MCP-activated NK-cells demonstrated functionality in inducing cancer cell death. MCP consisted of oligogalacturonic acids with some containing 4,5-unsaturated non-reducing ends. Conclusions MCP has immunostimulatory properties in human blood samples, including the activation of functional NK cells against K562 leukemic cells in culture. Unsaturated oligogalacturonic acids appear to be the immunostimulatory carbohydrates in MCP.